The impact of chronic kidney disease and short-term treatment with rosiglitazone on plasma cell-free DNA levels - McGuire, A.; Urosevic, N.; Chan, D.; Dogra, G.; Inglis, T.; Chakera, Aron (Hindawi Publishing Corporation, 2014)
© 2014 Amanda L. McGuire et al. Patients with chronic kidney disease (CKD) are at increased risk of cardiovascular disease. Circulating free nucleic acids, known as cell-free DNA (cfDNA), have been proposed as a novel biomarker of cardiovascular risk. The impact of renal impairment on cfDNA levels and whether cfDNA is associated with endothelial dysfunction and inflammation in CKD has not been systematically studied. We analysed cfDNA concentrations from patients with varying degrees of CKD. In addition, to determine whether there is a relationship between cfDNA, inflammation, and endothelial dysfunction in CKD, levels of proinflammatory cytokines and von Willebrand Factor (vWF) were measured in patients treated with the peroxisome proliferator-activated receptor gamma agonist rosiglitazone or placebo for 8 weeks. cfDNA levels were not increased with renal impairment or associated with the degree of renal dysfunction (P = 0.5). Treatment with rosiglitazone for 8 weeks, but not placebo, was more likely to lead to a reduction in cfDNA levels (P = 0.046); however, the absolute changes in cfDNA concentrations during treatment were not statistically significant (P > 0.05). cfDNA levels correlated with markers of endothelial dysfunction (hsCRP P = 0.0497) and vWF (P = 0.0005). In conclusion, cell-free DNA levels are not influenced by renal impairment but do reflect endothelial dysfunction in patients with CKD.